(Just) Transition Toward Climate Neutrality in Cities : A case study on Umeå, Northern Sweden - Nygren Laestander, Tilly (Malmö universitet, Institutionen för Urbana Studier (US), 2024)
The growth of cities is pressuring the extraction of scarce and precarious resources, leading to overexploitation. The international community is calling for a more holistic understanding of climate change responses in the urban context, including notions of gender equality and justice aspects. The case of this study, Umeå, is one of many places that are undergoing a transition toward climate neutrality. Umeå stands out and is renowned due to its take on climate mitigation, as well as on the committed approach to gender perspectives in city planning. The guiding aim of this thesis is to explore how the aims, efforts, projects and strategies of Umeå municipality take into account principles of justice in relation to the transition toward climate neutrality. Another aim is to explore how the findings from Umeå can contribute to further understanding of justice in transition within an urban context, a gap which earlier research has detected. The theoretical framework applied to the study is the Just Urban Transition (JUT) framework. Combining the concepts from environmental, climate, energy and urban justice with feminist and decolonial perspectives on knowledge production is my way of exploring the JUT-framework within an urban context. The data of the study consists of semi-structured interviews and documents. The findings from this study shows that justice aspects can be addressed in relation to transition processes without an explicit formulation derived from justice literature, and that feminist and decolonial perspectives on knowledge production can further strengthen the understanding of justice concepts. Examples where awareness of gender or socio-economic background intersects with climate mitigation have showcased the interconnectedness of how different justice perspectives can be translated into practice. Through a justice lens, this study detected that during the transition toward climate neutrality, Umeå emphasises cooperation through co-creation and dialogue-processes, with the aim to anchor ...